The Effectiveness of Student Learning Motivation Using Wordwall Media in Tutoring Services - Nur Syahira Agustina; Wanty Khaira (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
Learning motivation is an essential factor in academic achievement, yet many students still exhibit low engagement, lack of focus, and limited persistence. Similar conditions were found among Grade VIII students at SMP Negeri 1 Baitussalam, particularly during learning guidance sessions. To address this issue, interactive media that align with students’ needs are required. Wordwall, a game-based digital platform, offers a potential solution by creating a more engaging and participatory learning atmosphere. This study examined the effectiveness of Wordwall in enhancing students’ learning motivation within the context of guidance services. Using a quasi-experimental design with a one-group pretest–posttest, the research involved eight Grade VIII-4 students. The intervention consisted of Wordwall-based interactive quizzes, followed by a posttest to measure changes in motivation. The results revealed a significant improvement (p < 0.05) with an average N-Gain score of 0.90, categorised as high. The findings suggest that Wordwall effectively fosters students’ interest, activeness, and persistence. In addition, its application in guidance sessions provides new insights into the broader use of digital media beyond classroom instruction. These results offer practical implications for teachers and counsellors to integrate interactive technology more creatively in supporting student motivation and academic outcomes.